Double Heterotopic Pregnancies with Live Intrauterine Pregnancy after Ovarian Stimulation - S. Shi; M. Rasouli; A. Raman; G. de Guzman (Hindawi Limited, 2022)
Heterotopic pregnancies, although rare in natural conceptions, have increased in incidence with use of assisted reproductive techniques (ART). Double heterotopic pregnancy in addition to an intrauterine pregnancy is exceedingly rare. In this case, we present a patient who underwent ovulation induction and intrauterine insemination (IUI) and was found on ultrasound to have a live heterotopic pregnancy. Intraoperatively, both fallopian tubes were grossly swollen and engorged. Bilateral salpingectomy was performed. Pathology identified gestational products in both fallopian tubes consistent with a double heterotopic pregnancy. Postoperatively, the intrauterine pregnancy resulted in a live birth. Although double heterotopic pregnancy and an intrauterine pregnancy is exceedingly rare, this case emphasizes the importance of routinely inspecting the contralateral fallopian tube at the time of surgery for an ectopic pregnancy, particularly in patients undergoing ovulation induction.